The Structure of Intonational Meaning Evidence from English - Ladd, Jr (Indiana University Press, 1980)
The Structure of Intonational Meaning presents a linguistic study of English intonation, described in the original 1980 front flap as follows: "Using the data of English intonation, D. Robert Ladd, Jr., investigates the theoretical and methodological assumptions of past studies in the field. His impressive synthesis develops a new, comprehensive foundation for the study of English intonation in general. Ladd discusses a number of long-standing issues, including the relation of stress to intonation (and the associated questions of the phonological nature of sentence accent and the phonetic nature of stress), the various approaches to the placement of sentence accent, the phonological analysis of intonation contours into 'levels' or 'configurations', and the 'lexical' and 'syntactic' approaches to the meaning of intonation."